Hemoblastosis chemotherapy of malignant tumors and trenimon and vincaleukoblastin - Linke, A. (2015)
The results in 953 patients with malignant tumors hemoblastosis and treated with trenimon since 1958 and 112 patients treated with vincaleukoblastin reported.